Advocating Archives: An Introduction to Public Relations for Archivists - Finch, Elsie Freeman (Rowman & Littlefield Publishers, 1994)
Now in Paperback! As institutional budgets become tighter and information sources wider and more complex, archivists, manuscript curators and staff of special collections seek ways to broaden the use of their materials, bringing their services and their story to wider publics. Advocating Archives: An Introduction to Public Relations for Archivists presents practical advice on how to find and relate to these publics: how to better serve the client in person, launch a fund-raising campaign, work with the media, market programs, organize programs around historical events, train and successfully use volunteers, and avoid the most common public relations errors by planning. Written by archivists with previous professional or practical experience in these fields, Advocating Archives offers simply written, practical guidelines for the professional or manager who either develops their own public relations program or works with public relations professional in their institution. Three studies in archival public relations, taken from the daily experience of their writers, provide material for the instructors in archival management courses. Part of a long-term public relations initiative undertaken by the Society of American Archivists, the book aims to make public relations skills an integral part of archival management, and to help the archivist, curator, or special collections professional direct the public's response to their work.